2021
DOI: 10.5005/jp-journals-10005-2076
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Effect of Potassium Iodide and Glutathione on Tooth Discoloration after Application of 38% Silver Diamine Fluoride in Primary Molars: An In Vitro Study

Abstract: A bstract Aim To evaluate and compare the effect of potassium iodide (KI) and glutathione (GSH) on tooth discoloration after application of 38% silver diamine fluoride (SDF) in primary molars. Method: Total of 30 primary molars were randomly divided into three groups of 10 each. Teeth were prepared and divided into: Group A—SDF only, Group B—SDF followed immediately by application of KI, and Group C—SDF was mixed with 25 mg of GSH. Final restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…One in vitro investigation on extracted bovine teeth concluded that "GSH is more effective than KI in reducing discoloration in enamel and dentin" [20]. Two other in vitro studies were conducted on extracted human primary molars and premolars [21,22]. The primary teeth study suggested that the "SDF + GSH combination effectively reduces discoloration and can be used as an alternative to KI" [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One in vitro investigation on extracted bovine teeth concluded that "GSH is more effective than KI in reducing discoloration in enamel and dentin" [20]. Two other in vitro studies were conducted on extracted human primary molars and premolars [21,22]. The primary teeth study suggested that the "SDF + GSH combination effectively reduces discoloration and can be used as an alternative to KI" [21].…”
Section: Discussionmentioning
confidence: 99%
“…The other two studies were performed in vitro on carious primary molars and demineralized enamel of premolar teeth [21,22]. Effective reduction in discoloration with GSH was reported in the study conducted with extracted and carious primary molars [21]. However, the study conducted with arti cial enamel caries teeth indicated no statistically signi cant effect of the SDF + GSH combination on color change [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently released Riva Star™ compensates for this drawback by reducing staining by applying KI. Several studies have shown that the application of KI is effective in reducing discoloration after SDF [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…GDF ile karıştırılarak diş yüzeyine uygulanmaktadır. 51 KI; beyaz veya şeffaf, 6 yüzlü kristaller oluşturan, %76 iyot ve %23 potasyumdan oluşan bir tuzdur. Işığa oldukça duyarlıdır, kısmen higroskopiktir ve suda çözünmektedir.…”
Section: Glutatyon Ve Kiunclassified